Phytosociology of the herbaceous flora of university of ibadan oil palm plantation, University of Ibadan, Ibadan, Southwest, Nigeria (2023)
Plantation agriculture perturbs native flora of ecosystems. This impacts vegetation biodiversity, through species invasion and shift in weeds population dynamics. Oil palm plantations are common in tropical landscapes, and can cause long-term floristic changes. There is paucity of knowledge on inventory and potential impacts of the plantation on community structure of plants. This study investigated herbaceous flora diversity and phytosociology as indicators of appropriateness of management strategy in the University of Ibadan oil palm plantation. The study site is located in a lowland rainforest at the Teaching and Research Farm, University of Ibadan, Ibadan, Nigeria on 07°27`253`N latitude and longitude 03°53`427`E. A systematic sampling was employed to enumerate herbaceous flora of a hectare mega plot. The hectare was laid along 100 m transects at 10 m intervals, with 10 m separating each transect. Each transect was laid to cut across middle of 9 m x 9 m x 9 m plant spacing for oil palm. Data were collected on species composition, frequency and density for determination of relative importance value (RIV), species diversity, ordination and classification. The plantation consisted of 32 herbaceous species in 15 plant families. Commelina erecta had the highest RIV (12.621) while Alchornea cordifolia had the least (RIV=0.288). Diversity indices indicated high species richness (Simpson Index = 0.909) among enumerated species and species co-dominance (D = 0.091) Ordination biplots indicated three distinct vegetation structures (Secondary, wetland, dryland/fallow). Classification model showed Commelina erecta had widest coverage of 92% in distribution at the site followed by Commelina benghalensis at 88%. The Oil palm plantation is heterogeneous in species composition, and was not detrimentally invaded. Weeding regimes and other agronomic practices in the plantation should be ecologically integrated to conserve its native vegetation.